Meeting first-time buyers’ housing needs and preferences in greater Kuala Lumpur - Tan, Teck-Hong * (Elsevier Ltd, 2012)
The high prices of houses in Greater Kuala Lumpur have made it difficult for first-time homebuyers to own a house. As a result, affordable housing schemes were introduced recently to help them become home owners. The Malaysian government has launched many kinds of public low-cost housing schemes; however, many housing projects which resulted from these schemes have turned into slums that do not provide wholesome environment for families to live. In order to avoid building more slums and benefit more young buyers from the scheme, the goal of this paper is to determine the right housing attributes required for first-time homebuyers in the urban area. A total of 300 questionnaires were distributed to young Malaysians in Greater KL with 265 questionnaires were returned. Results revealed that accessibility and neighborhood environment play a role in the decision to own. It can also be seen that ecologically friendly homes that embrace sustainability were important considerations when buying a home.